A Pilot Study of Circulating Endothelial and Hematopoietic Progenitor Cells in Children With Sarcomas. Issue 6 (August 2015) - Pradhan, Kamnesh R.; Mund, Julie A.; Claussen, Heather L.; Gosiengfiao, Yasmin C.; Radulescu, Vlad C.; Ballard, Jennifer J.; Liu, Ziyue; Vik, Terry A.; Case, Jamie
<x xml:space="preserve">Abstract</x> Utilizing a multiparametric flow cytometry protocol, we assessed various cell types implicated in tumor angiogenesis that were found circulating in the peripheral blood of children with sarcomas (cases) based on their cell surface antigen expression. Circulating endothelial cells (CECs), endothelial colony-forming cells (ECFCs), and the ratio of 2 distinct populations of circulating hematopoietic stem and progenitor cells (CHSPCs), the proangiogenic CHSPCs (pCHSPCs) and nonangiogenic CHSPCs (nCHSPCs) were enumerated. Multiparametric flow cytometry was analyzed in cases at baseline and at 4 additional timepoints until the end of treatment and levels compared with each other and with healthy controls. At all timepoints, cases had significantly lower levels of CECs, but elevated ECFCs and a pCHSPC:nCHSPC ratio compared with controls (all P-values <0.05). There was no significant difference in any of the cell types analyzed based on tumor histology, stage (localized vs. metastatic), or tumor size. After treatment, only the CECs among the complete responders were significantly lower at end of therapy (P<0.01) compared with nonresponders, whereas the ECFCs among all cases significantly increased (P<0.05) compared with baseline. No decline in the pCHSPC:nCHSPC ratio was observed despite tumor response. On the basis of these results, a validation of CECs as prognostic biomarker is now warranted.